Electrode composite body, manufacturing method of the same, polymer composition, and battery
The electrode composite with a polymer layer addresses the issues of dendrite formation and low conductivity in metallic Li batteries by enhancing ion conductivity and safety, achieving higher energy density.
Patent Information
- Application Number
- JP2024102611
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-28
- Filing Date
- 2024-06-26
- Publication Date
- 2025-01-20
AI Technical Summary
Existing electrode composites using metallic Li as the negative electrode face issues such as high reactivity, formation of metal dendrites, and low ionic conductivity, leading to safety risks and reduced battery performance.
An electrode composite with a polymer layer containing an aromatic ring and heteroatoms, having specific ionic conductivity, porosity, and surface roughness, along with a region of atomic ratio of Li+ and F-, is developed to suppress dendrite growth and enhance conductivity.
The composite effectively suppresses dendrite growth and improves ionic conductivity, resulting in a safer and higher energy density secondary battery.
Smart Images

Figure 2025009961000015 
Figure 2025009961000001 
Figure 2025009961000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode composite and a method for producing the same, a polymer composition, and a battery. [Background technology]
[0002] In recent years, portable electronic devices have become smaller and more functional. This has led to a demand for higher energy density in the secondary batteries that power these devices. If metallic Li could be used for the negative electrodes of secondary batteries, it is expected that the capacity of these batteries would be significantly higher than that of current lithium-ion batteries.
[0003] However, many challenges remain before batteries with metallic Li as the anode can be put to practical use. Metallic Li is highly reactive, and reacts with water, oxygen, and nitrogen during the battery manufacturing process, causing variations in electrode performance. In addition, repeated charging and discharging of metallic anodes can lead to problems such as the formation of metal dendrites and the decomposition of the electrolyte due to the high reactivity. If the dendrites grow and reach the positive electrode, there is a risk of fire due to a short circuit.
[0004] In response to such problems, Patent Document 1 discloses an electrode composite including a lithium metal layer and a porous polymer layer attached to one surface of the lithium metal layer. Patent Document 2 discloses a short-circuit prevention layer for an all-solid-state secondary battery including a heat-resistant resin having ion conductivity. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2004-134403 A [Patent Document 2] JP 2021-163622 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the polymer layer of Patent Document 1 does not have the function of suppressing dendrites due to its porosity, and the polymer layer of Patent Document 2 has low ionic conductivity and cannot be used at a practical high current density.
[0007] Therefore, an object of the present invention is to provide an electrode composite that extends the life of a battery using a metallic Li negative electrode, a method for producing the same, a polymer composition, and a battery. [Means for solving the problem]
[0008] In order to solve the above problems, the present invention includes the following [I] to [XXII]. [I] An electrode composite having a polymer layer and an electrode adjacent to at least one surface of the polymer layer, the electrode including metal Li or a current collector, a polymer constituting the polymer layer including an aromatic ring and a heteroatom in a main chain, and an ionic conductivity of the polymer layer being 1.0×10 -6 the porosity of the polymer layer observed by cross-sectional SEM is 0% or more and 10% or less, and the arithmetic mean roughness Ra of the surface of the polymer layer is 0 μm or more and 1.0 μm or less. [II] Li, as measured by X-ray photoelectron spectroscopy (XPS) analysis + Atomic ratio and F - The electrode composite described in [I], wherein a region in which both atomic ratios are 5% or more and 50% or less is present on the surface layer of the side of the polymer layer having the electrode in close proximity thereto, or is present between the polymer layer and the electrode. [III] The electrode composite according to [I] or [II], wherein the solvent content in the polymer layer is from 0% by weight to 60% by weight. [IV] The electrode complex according to [III], wherein the solvent includes one or more of N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethylacetamide (DMAc), dimethylsulfoxide (DMSO), and sulfolane. [V] The electrode composite according to any one of [I] to [IV], wherein the polymer is an aromatic polyamide having a structure of the following chemical formula:
[0009] [ka]
[0010] Ar1 and Ar2 are structures containing an aromatic ring in a part of the main chain. Ar1 and Ar2 may be the same structure or different structures. For example, Ar1 and Ar2 may have a plurality of aromatic rings bonded by an ether bond or the like, or a non-aromatic bonded to an aromatic ring may be included in the main chain. [VI] The electrode composite according to [V], wherein the aromatic polyamide has a structure of the following chemical formula:
[0011] [ka]
[0012] R1 to R4 are each a functional group composed of one or more of C, H, O, N, Si, S, and halogen atoms. [VII] The electrode composite according to any one of [I] to [VI], wherein the polymer is a polymer having a thiourea group. [VIII] The electrode composite according to any one of [I] to [VII], wherein the polymer layer has a thickness of 0.1 μm or more and 50.0 μm or less. [IX] The electrode composite according to any one of [I] to [VIII], wherein the average lithium atomic ratio of the polymer layer is 0.005 or more and 1.0 or less. [X] A polymer composition comprising a polymer whose main chain contains aromatic and heteroatoms, and a solvent. [XI] The polymer composition according to [X], which contains a fluorine generating agent. [XII] The polymer composition according to [X] or [XI], wherein the polymer has a thiourea group. [XIII] The polymer composition according to any one of [X] to [XII], wherein the solvent includes a solvent having a boiling point of 0°C or higher and lower than 150°C. [XIV] The polymer composition according to any one of [X] to [XIII], wherein the solvent comprises solvent A having a boiling point of 0°C or more and less than 150°C, and solvent B having a boiling point of 150°C or more and 300°C or less. [XV] The polymer composition according to [XIV], wherein the solvent A and the solvent B are an azeotropic composition. [XVI] The polymer composition according to any one of [X] to [XV], wherein the polymer is an aromatic polyamide. [XVII] The polymer composition according to any one of [X] to [XVI], having an inherent viscosity of 1.5 dl / g or more and 10 dl / g or less. [XVIII] The polymer composition according to any one of [X] to [XVII], wherein the weight ratio of the polymer is 0.1% by weight or more and 13.0% by weight or less. [XIX] The polymer composition according to any one of [X] to [XVIII], which has a moisture content of 0 ppm or more and less than 200 ppm. [XX][X] to [XIX]. A method for producing an electrode composite, comprising a step of applying the polymer composition according to any one of the above to an electrode. [XXI] [I] to [IX] A battery comprising the electrode composite according to any one of the above. [XXII] [XXI] A vehicle, unmanned transport aircraft, electronic device, or power storage device comprising the battery described in. Effect of the Invention
[0013] According to the present invention, it is possible to provide an electrode composite that can be used as an electrode for a secondary battery having a high energy density and is safe by suppressing the reaction between the surface of metallic lithium and the atmosphere or an electrolyte and the growth of dendrites during charging and discharging. In addition, it is possible to provide a battery having a high energy density and is safe by using the electrode composite as an electrode and a separator at the same time. [Brief description of the drawings]
[0014] [Figure 1] 1 shows the measurement results of X-ray photoelectron spectroscopy (XPS) analysis of Example 16. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described in detail.
[0016] An electrode composite according to an embodiment of the present invention is an electrode composite having a polymer layer and an electrode adjacent to at least one surface of the polymer layer, the electrode including metal Li or a current collector, a polymer constituting the polymer layer including an aromatic ring and a heteroatom in a main chain, and an ionic conductivity of the polymer layer being 1.0×10 -6 The electrode composite has a surface roughness Ra of 0 μm or more and 1.0 × 10 S / cm or less, a porosity of the polymer layer observed with a cross-sectional scanning electron microscope (SEM) of 0% or more and 10% or less, and an arithmetic mean roughness Ra of the surface of the polymer layer of 0 μm or more and 1.0 μm or less.
[0017] A polymer composition according to an embodiment of the present invention is a polymer composition having a polymer whose main chain contains aromatic and heteroatoms, and a solvent.
[0018] In the embodiment of the present invention, the electrode composite can be used as an electrode that is a component of a battery.
[0019] The electrode composite according to the embodiment of the present invention is preferably used as a positive electrode or a negative electrode for a secondary battery, but since it contains metallic Li, it is more preferable to use it as a negative electrode. In addition, since the electrode composite including the current collector can also be used as an anode-less electrode, it is preferable to use it as a negative electrode. In the embodiment of the present invention, the secondary battery is a general term for a chemical battery that can be repeatedly charged and discharged two or more times. A secondary battery is constituted by a positive electrode, a negative electrode, and a separator that electrically separates them so that they do not short-circuit, as minimum components.
[0020] In the present invention, the positive electrode may be any material. Specific positive electrode materials include, but are not limited to, inorganic substances such as metal oxides and metal sulfides of nickel, lithium, cobalt, and manganese, carbon materials such as graphite, carbon, and CNT, and carbon materials carrying metals, and air electrodes using oxygen in the air as a positive electrode active material. These positive electrode materials may also be used in combination with a current collector. In the present invention, the negative electrode material is not particularly limited to, but includes, for example, simple metals such as lithium, sodium, aluminum, magnesium, and zinc, carbon materials and inorganic substances carrying these metals, and the like. The negative electrode material may also be used in combination with a current collector. The separator is not particularly limited to, but includes, for example, a microporous membrane, a gel electrolyte, and a solid electrolyte. In addition, the polymer layer in the electrode composite according to the embodiment of the present invention can be used as a separator, and may be used in combination with the above-mentioned separator member, or the above-mentioned separator member can be omitted.
[0021] Furthermore, the secondary battery in the embodiment of the present invention may contain an electrolyte or a solid electrolyte in addition to the positive electrode, the negative electrode, and the separator. An electrolyte is a general term for a substance that conducts specific ions by dissolving in a solvent. As the solvent, any solvent such as an organic solvent or an aqueous solvent can be selected as necessary. A solid electrolyte is an electrolyte that can conduct ions without containing a solvent. Examples of such a solid electrolyte include a gel electrolyte and an inorganic solid electrolyte.
[0022] Furthermore, the secondary battery according to the embodiment of the present invention may contain any additives other than the positive electrode, negative electrode, separator, and electrolyte for the purpose of stable operation of the battery.
[0023] Specific examples of such secondary batteries include lead acid batteries, nickel-metal hydride batteries, nickel-cadmium batteries, lithium ion batteries, sodium ion batteries, nickel-iron batteries, nickel-zinc batteries, lithium metal batteries, lithium metal-air batteries, aluminum metal-air batteries, sodium sulfur batteries, zinc-air batteries, sodium metal-air batteries, and lithium sulfur batteries. Among these batteries, those using simple metals such as lithium, sodium, aluminum, and zinc as the negative electrode are preferred from the viewpoint of excellent weight energy density, and lithium metal is most preferred. Furthermore, lithium metal-air batteries, sodium metal-air batteries, and zinc-air batteries using an air electrode as the positive electrode are more preferred from the viewpoint of increasing weight energy density.
[0024] Examples of electrolytes preferably used in lithium ion batteries include lithium salts such as LiPF6, LiAsF6, LiClO4, LiBF4, LiBr, lithium bis(oxalate)borate, lithium difluoro(oxalate)borate, lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(pentafluoroethanesulfonyl)imide, etc. These lithium salts may be used alone or in combination of two or more.
[0025] Specific examples of solvents that dissolve these electrolytes include carbonate-based solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC), sulfur-containing solvents such as dimethyl sulfoxide (DMSO) and sulfolane, lactones such as γ-butyl lactone, ether-based solvents such as tetrahydrofuran (THF), dioxane, and 1,3-dioxolane (DOL), and aqueous solvents such as water and methanol. These may be used alone, or two or more types may be appropriately mixed together for the purpose of adjusting the potential stability and viscosity. In addition, different electrolyte solutions or mixtures thereof may be used on the positive electrode side and the negative electrode side via a separator.
[0026] The electrode composite in the embodiment of the present invention has a polymer layer and an electrode on at least one side of the polymer layer in close proximity. Here, "in close proximity" preferably means that at least one of the positive electrode and the negative electrode of the present invention and the ion-conducting polymer membrane are in close proximity. The polymer layer of the present invention is in close proximity to at least one of the electrodes, thereby suppressing deterioration of the electrode surface during the battery manufacturing process and when the battery is used, and short circuiting and ignition due to dendrite generation when the battery is used. Here, "in close proximity" means being within 1 μm, and may be in direct contact or may be present via another layer. Specific examples of other layers include an SEI layer (Solid Electrolyte Interphase) formed by a reaction on the electrode surface, an inorganic layer, and the like.
[0027] The electrode composite of the present invention has a Li + Atomic ratio and F - It is preferable that the region in which the atomic ratios of both are 5% to 50% exists in the surface layer of the polymer layer having the electrode in close proximity thereto, or exists between the polymer layer and the electrode. + Atomic ratio and F - By having the atomic ratio in the above range, it is possible to improve the effect of suppressing the growth of Li dendrites while maintaining ion conductivity. + Atomic ratio and F - The atomic ratio is the ratio of Li to the total number of atoms detected in each region by XPS. + Atoms and F - The ratio of the number of atoms. Li + Atoms and F - The atoms do not include non-ionized Li metal atoms or covalently bonded F atoms such as C—F bonds. The phrase "present on the surface of the polymer layer adjacent to the electrode" means that the Li atoms are present within a depth of 300 nm from the surface of the polymer layer adjacent to the electrode in the XPS analysis described below. + Atomic ratio and F -The region where the atomic ratios are between 5% and 50% is thought to contain a large amount of LiF, and it is believed that the presence of a large amount of LiF improves battery life and performance by suppressing the growth of dendrites while providing high ionic conductivity.
[0028] In addition, when the electrode composite of the present invention is used as an electrode for a battery, the polymer layer in the electrode composite is preferably present on the surface close to the other electrode side. By disposing a polymer layer on the other electrode side of the electrode using the electrode composite, short circuits and fires due to dendrite generation during use of the battery can be further suppressed. In addition, the polymer layer is preferably present only on the surface close to the other electrode side of the electrode using the electrode composite. By having the polymer layer only on the surface close to the other electrode side of the electrode using the electrode composite, the electronic conductivity of the surface not having the polymer is improved, and the capacity of the produced battery is improved.
[0029] The electrode composite in the embodiment of the present invention has a polymer layer, and the polymer constituting the polymer layer contains an aromatic ring and a heteroatom in the main chain. When an electrolyte is used in a secondary battery, a known polymer can be used as necessary as long as it does not dissolve in the electrolyte. Specific examples include polycarbonate, polyacetal, polyester, polysulfone, polyarylate, polyurethane, polyimide, polyamide (including polyamic acid), polyarylene sulfide, polyphenylene sulfide, polyamideimide, polyetheretherketone, polyetherimide, polyethersulfone, polyarylene ether, polyarylene ether ketone, and other polyethers, polyethylene, polypropylene, vinyl polymers including polymethyl methacrylate, and alloys and copolymers thereof. The polymer layer included in the electrode composite according to the embodiment of the present invention is preferably composed of one or more selected from the group consisting of polyphenylene sulfide, polyamide, polyarylene ether, polyethersulfone, polyimide, polyamideimide, polyarylene ether ketone, and copolymers thereof, from the viewpoint of excellent heat resistance. From the viewpoint of excellent moldability, polyamide, polyphenylene sulfide, polyamideimide, and polyethersulfone are more preferable, and among these, aromatic polyamide, aromatic polyimide, and aromatic polyamideimide are particularly preferable from the viewpoint of excellent heat resistance and solvent resistance, and among these, aromatic polyamide (aramid) is the most preferable from the viewpoint of high strength. These polymers may be used alone or in combination. For example, different types of polymers may be copolymerized, or may be alloyed in the film.
[0030] Polyamides, polyimides, and polyamideimides that can be suitably used in the embodiments of the present invention preferably include polymers having a structure represented by any one of the following chemical formulas (1) to (3): Aromatic polyamides include those having a repeating unit represented by the following chemical formula (1), aromatic polyimides include those having a repeating unit represented by the following chemical formula (2), and aromatic polyamideimides include those having a repeating unit represented by the following chemical formula (3).
[0031] [ka]
[0032] [ka]
[0033] [ka]
[0034] Here, Ar1 and Ar2 in chemical formulas (1) to (3) are structures containing an aromatic ring in a part of the main chain. Ar1 and Ar2 may be the same structure or different structures. For example, Ar1 and Ar2 may have a plurality of aromatic rings bonded by ether bonds or the like, and a non-aromatic bonded to an aromatic ring may be included in the main chain. Note that the aromatic ring is a general term including aromatic hydrocarbons, which are cyclic unsaturated organic compounds such as benzene, or heteroaromatic compounds containing elements other than carbon in the ring structure.
[0035] The bonds constituting the main chain on the aromatic rings contained in Ar1 and Ar2 may be meta-, para-, or ortho-oriented. Furthermore, some of the hydrogen atoms on the aromatic rings contained in Ar1 and Ar2 may be substituted with any functional group. Examples of such functional groups include a hydroxyl group, an ether group, a thioether group, a carboxyl group, a phosphine group, and a sulfone group.
[0036] The polymer contained in the electrode composite of the present invention is preferably the aromatic polyamide, and -CO-Ar2-CO- in chemical formula (1) preferably has the structure of the following chemical formula. By having the following structure, the polymer chain has a broadened rigid structure, improving dendrite resistance. Furthermore, the polymer contained in the electrode composite of the present invention may have a structure of aromatic polyamideimide, aromatic polyimide, semi-aromatic polyamide, semi-aromatic polyamideimide, semi-aromatic polyimide, aliphatic polyamide, aliphatic polyamideimide, or aliphatic polyimide, other than aromatic polyamide.
[0037] [ka]
[0038] R1 to R4 are each a functional group composed of one or more of C, H, O, N, Si, S, and halogen atoms.
[0039] Specific examples of aromatic diamines constituting aromatic polyamides, aromatic polyamideimides, and aromatic polyimides include, but are not limited to, paraphenylenediamine, metaphenylenediamine, orthophenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl, 2,2'-ditrichloromethyl-4,4'-diaminobiphenyl, 4,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, 2-chloro-1,4-phenylenediamine, 2-trifluoromethyl-1,4-phenylenediamine, 5-trifluoromethyl-1,3-phenylenediamine, 4,'-oxybis(3-trifluoromethyl)aniline, 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, 1,5'-naphthalenediamine, and 4,4'-diaminodiphenyl sulfone.
[0040] Specific examples of non-aromatic diamines include, but are not limited to, ethylenediamine, propanediamine, butanediamine, pentanediamine, and hexamethylenediamine.
[0041] The electrode composite in the embodiment of the present invention has a polymer layer, and the polymer constituting the polymer layer preferably has at least one of a thiocarbonyl group, a thiourea group, a thioamide group, and a thiourethane group, and a thiourea group is particularly preferred. By having the above functional group, the interaction between the polymer and the anion increases, and the cationic transport number improves. The improvement in the cationic transport number reduces decomposition products during battery operation, and improves the battery life. In particular, a polymer having an aromatic ring on the main chain can be suitably used as the polymer constituting the polymer layer. Examples of the polymer having an aromatic ring on the main chain include aromatic polythioketone, aromatic polythiourea, aromatic polythioamide, aromatic polythiourethane, semi-aromatic polythioketone, semi-aromatic polythiourea, semi-aromatic polythioamide, and semi-aromatic polythiourethane. A blend of multiple polymers may also be used. Among them, aromatic polythiourea, aromatic polythioamide, aromatic polythiourethane, and semi-aromatic polythiourea are more preferred, and aromatic polythiourea is particularly preferred, because they are easy to maintain high strength when thinned. That is, it is preferable that the ion-conducting polymer according to the embodiment of the present invention contains aromatic polythiourea.
[0042] Examples of aromatic polythioureas and semi-aromatic polythioureas that can be suitably used in the present invention include those having repeating units represented by the following chemical formula (7), chemical formula (8) and / or chemical formula (9). Ar1 in chemical formula (7), Ar1 and Ar 2、Ar1 in chemical formula (9) is a group containing an aromatic group, and may be a single group or a multi-component copolymer with multiple groups. R in chemical formula (9) is a non-aromatic structure that does not contain an aromatic ring. By using the above aromatic polythiourea or semi-aromatic polythiourea, the performance of blocking the permeation of substances other than ions that contribute to the operation of the battery is improved. Among the following chemical formulas (7), (8) and / or (9), chemical formulas (7) and (8) are more preferable. In addition, the bonds constituting the main chain on the aromatic ring may be either meta-oriented or para-oriented. Furthermore, some of the hydrogen atoms on the aromatic ring may be substituted with any group.
[0043] [ka]
[0044] [ka]
[0045] [ka]
[0046] Specific examples of aromatic diamines constituting aromatic polythiourea, aromatic polythioamide, and aromatic polythiourethane include, but are not limited to, paraphenylenediamine, metaphenylenediamine, orthophenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl, 2,2'-ditrichloromethyl-4,4'-diaminobiphenyl, 4,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, 2-chloro-1,4-phenylenediamine, 2-trifluoromethyl-1,4-phenylenediamine, 5-trifluoromethyl-1,3-phenylenediamine, 4,'-oxybis(3-trifluoromethyl)aniline, 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, 1,5'-naphthalenediamine, and 4,4'-diaminodiphenyl sulfone.
[0047] Specific examples of non-aromatic diamines include, but are not limited to, ethylenediamine, propanediamine, butanediamine, pentanediamine, and hexamethylenediamine.
[0048] The air permeability of the polymer layer of the electrode composite according to the embodiment of the present invention is preferably 1000 sec / 100 cc or more. The air permeability is more preferably 5000 sec / 100 cc or more, and even more preferably 10000 sec / 100 cc or more. If the air permeability is less than 1000 sec / 100 cc, the polymer ion conductive membrane often has physical through holes, and in addition to the effect of blocking the penetration of dendrites and the like may not be obtained, it is likely to be difficult to suppress liquid permeation. If the air permeability is 1000 sec / 100 cc or more, it is easy to block the penetration of dendrites and the like, and it is also easy to suppress liquid permeation, which is preferable. In order to set the air permeability in this range, it is preferable to form the polymer membrane by the manufacturing method described below.
[0049] The ionic conductivity of the polymer layer according to the embodiment of the present invention is 1.0×10 -6The ionic conductivity here refers to a value measured in a 25°C environment using a measuring method described below. The ionic conductivity is preferably 1.5×10 -5 S / cm or more is preferable, and 5.0×10 -5 More preferably, it is 1.0×10 -4 More preferably, it is 1.4×10 S / cm or more. -4 More preferably, it is 2.0×10 -4 More preferably, it is 5.0×10 S / cm or more. -4 More preferably, it is 1.0×10 -3 By setting the ionic conductivity within the above range, the ionic permeability inside the battery is high, and excellent output characteristics and cycle characteristics can be obtained. -6 If the ionic conductivity is less than 1.0×10 S / cm, the ionic permeability is low, the output characteristics are deteriorated, and the capacity may be significantly deteriorated when the battery is used repeatedly. The higher the ionic conductivity, the better. The upper limit is not particularly limited, but it is generally 1.0×10 S / cm or less. In order to set the ionic conductivity in this range, a preferred method is to form a polymer layer using a polymer described later, or to add a Li salt to the polymer layer.
[0050] The polymer layer in the embodiment of the present invention has a porosity of 10% or less as observed by cross-sectional SEM. The smaller the porosity, the more the precipitation of metallic Li inside the pores can be suppressed, and the more the short circuit of the battery can be prevented. It is preferably 5% or less, more preferably 2% or less, and particularly preferably 1% or less. The lower limit of the porosity is 0% by definition. There is no particular limitation on the method for reducing the porosity, but examples of the method include making the polymer used during film formation have a preferred structure and logarithmic viscosity, and setting the drying conditions during film formation to the preferred method described below. The measurement method of cross-sectional SEM will be described later.
[0051] Furthermore, the arithmetic mean roughness Ra of the surface of the polymer layer in the embodiment of the present invention is 1.0 μm or less. The small surface roughness allows the deposition of metallic Li to be uniform, and prevents short-circuiting of the battery. The surface roughness is more preferably 0.5 μm or less, even more preferably 0.1 μm or less, and even more preferably 0.05 μm or less. The lower limit is 0 μm by definition. There are no particular limitations on the method for making the surface roughness relatively small, but examples include using the solvent composition and drying conditions in the polymer composition as the preferred composition and method described below.
[0052] Furthermore, in the electrode composite according to the embodiment of the present invention, the solvent content in the polymer layer is preferably 0% by weight or more and 60.0% by weight or less, more preferably 0% by weight or more and 30.0% by weight or less, even more preferably 0% by weight or more and 20.0% by weight or less, even more preferably 0% by weight or more and 10.0% by weight or less, and even more preferably 0% by weight or more and 5.0% by weight or less. By keeping the solvent content within the above range, the polymer layer can exhibit good ion conductivity while suppressing decomposition of the solvent on the surface of the metallic Li.
[0053] Further, in the electrode composite according to the embodiment of the present invention, the solvent content in the polymer layer is more preferably 0% by weight or more and 5.0% by weight or less. By further reducing the solvent content, it is possible to suppress the decomposition of the solvent on the surface of the metal Li, and the battery life is improved. It is more preferably 3.0% by weight or less, and particularly preferably 1.0% by weight or less. The lower limit of the solvent content is, by definition, 0% by weight, and is preferably 0.1% by weight or more. The solvent content can be calculated from the weight loss rate of a thermogravimetric differential thermal analyzer (TG-DTA) in the method described below. The method for reducing the solvent content is not particularly limited, but for example, a method of reducing the amount of solvent remaining in the polymer layer by setting the solution composition and drying conditions during film formation to the preferred composition and method described below can be mentioned.
[0054] Furthermore, in the embodiment of the present invention, the solvent in the polymer layer in the electrode complex is preferably a solvent containing one or more of N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethylacetamide (DMAc), dimethylsulfoxide (DMSO), and sulfolane. The solvent contained in the electrode complex can be identified by NMR measurement. The method of including the above-mentioned solvent in the electrode complex is not particularly limited, but for example, the above-mentioned solvent may be added to the solution composition during film formation.
[0055] Further, in the embodiment of the present invention, the thickness of the polymer layer is preferably 0.1 μm or more and 50.0 μm or less, more preferably 0.2 μm or more and 50.0 μm or less, more preferably 0.3 μm or more and 50.0 μm or less, more preferably 0.5 μm or more and 50.0 μm or less, more preferably 0.3 μm or more and 50.0 μm or less, more preferably 0.3 μm or more and 10 μm or less, more preferably 1.0 μm or more and 5.0 μm or less, and particularly preferably 0.3 μm or more and 3.0 μm or less. By setting the thickness of the polymer layer within the above range, it is possible to suppress the precipitation of dendrites during charging and discharging while reducing the resistance of ion conduction of the electrode composite, and it is possible to achieve both the discharge capacity and the life of the battery. The thickness of the polymer layer is not particularly limited to the above range, but for example, the concentration of the polymer contained in the solution during film formation is set to the above-mentioned preferred conditions, and the coating thickness is set to the above-mentioned preferred conditions.
[0056] Further, the average lithium atomic ratio of the polymer layer in the embodiment of the present invention is preferably 0.005 to 1.0, more preferably 0.01 to 0.6, even more preferably 0.01 to 0.5, even more preferably 0.02 to 0.5, even more preferably 0.05 to 0.5, and particularly preferably 0.07 to 0.5. The average lithium atomic ratio represents the ratio of lithium to all atoms contained in the polymer layer. The larger the average lithium atomic ratio of the polymer layer, the smaller the resistance of ion conduction of the electrode composite, and the higher the discharge capacity becomes. In particular, an electrode composite having an average lithium atomic ratio within the above range can be particularly preferably used in an all-solid-state battery that does not use an electrolyte. The smaller the average lithium atomic ratio of the polymer layer, the higher the strength of the polymer layer, so that precipitation of dendrites during charging and discharging can be suppressed, and the battery life is improved. The average lithium atomic ratio of the polymer layer can be measured by Rutherford backscattering spectroscopy (RBS) measurement described later. The method for adjusting the average lithium atomic ratio of the polymer layer to fall within the above range is not particularly limited. For example, a method for incorporating lithium element into the polymer layer includes adding a Li salt to a solution during film formation at a preferred concentration described below.
[0057] The lithium element contained in the polymer layer in the embodiment of the present invention may be added in the polymer film in the form of a lithium salt as an electrolyte. From the viewpoint of thermal and electrochemical stability, the lithium salt is preferably LiPF6, LiAsF6, LiClO4, LiBF4, LiBr, lithium bis(oxalate)borate, lithium difluoro(oxalate)borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide, or the like. These lithium salts may be used alone or in combination of two or more. One or more metal elements selected from the group consisting of sodium, magnesium, zinc, and aluminum contained in the polymer ion conductive film in the embodiment of the present invention may also be added in the polymer film in the form of a salt as an electrolyte.
[0058] The polymer layer in the embodiment of the present invention preferably contains a fluorine generator. - A compound that generates ions, mainly containing F atoms. By including a fluorine generator, the battery can operate stably even under high current density conditions, and the battery life is improved. Specific examples of fluorine generators include LiPF6, LiBF4, LiTFSI, LiFSI, and fluoroethyl carbonate. F - LiPF6, LiFSI, and fluoroethyl carbonate, which are likely to generate ions, are more preferable, LiPF6 and fluoroethyl carbonate are further preferable, and LiPF6 is particularly preferable. The above effect is achieved by using F - It is believed that this is achieved by generating ions, which causes the metallic Li surface to react with F-ions, resulting in the formation of LiF near the interface, which then reduces the interface resistance. Methods for incorporating a fluorine generator into the polymer layer include adding the fluorine generator to the coating solution used to form the polymer layer, and immersing the electrode composite in a solution containing the fluorine generator. In addition, in general, F - When ions are generated, F - There is a tendency to avoid including a fluorine generating agent in a battery because there is a possibility that the ions react with the positive electrode material, resulting in a decrease in the battery capacity and lifespan. However, since the polymer layer in the embodiment of the present invention has a small porosity, it is possible to prevent F- ions generated on the metal Li surface from reaching the positive electrode side, and therefore F - This makes it possible to avoid the occurrence of a decrease in the lifespan caused by the reaction between the ions and the positive electrode material, and instead makes it possible to improve the lifespan of the battery.
[0059] The polymer layer in the embodiment of the present invention is preferably produced by a production method including a step of allowing the polymer layer to contain a fluorine generating agent and then leaving the polymer layer at rest at 40° C. or higher. -In order to promote the generation of ions, 50°C or higher is more preferable, and 60°C or higher is particularly preferable. The time of standing at the above temperature is preferably 2 hours or more, more preferably 6 hours or more, more preferably 12 hours or more, and particularly preferably 24 hours or more. In order to suppress the interfacial peeling between the polymer layer and the metallic lithium, the standing at the above temperature is preferably under pressurized conditions. Specifically, 0.1 MPa or more is preferable, 0.5 MPa or more is more preferable, 1.0 MPa or more is more preferable, 3.0 MPa or more is more preferable, and 5.0 MPa or more is particularly preferable. Standing at the above temperature may be performed after the battery is fabricated.
[0060] The electrode composite in the embodiment of the present invention may contain an inorganic ion conductor. In order to improve dendrite resistance and reduce interface resistance, it is preferable to configure the inorganic ion conductor, polymer layer, and metallic Li in that order. This is because while the inorganic ion conductor has high ion conductivity, it is inferior to the above-mentioned polymer layer in dendrite resistance and interface resistance. On the other hand, an electrode composite combining these can achieve both high ion conductivity and dendrite resistance, contributing to a secondary battery that has both safety and high performance. Known inorganic ion conductors can be appropriately used, and examples of inorganic solid electrolytes include Li2S-P2S5 and Li7P3S. 11 and oxide-based solid electrolytes such as LiI and Li2O-B2O3-P2O5. The shape of the inorganic ion conductor is not particularly limited, but when used in an electrode composite, it is generally preferable to use one that is coated or molded into a sheet.
[0061] One embodiment of the present invention is a battery having the above-mentioned electrode composite as an electrode. In particular, it is preferably used as a secondary battery. In the secondary battery, the preferred embodiment of the electrode composite is the same as described above. Since the above-mentioned electrode composite has both low ion resistance and excellent dendrite resistance, a secondary battery using this electrode composite can achieve both high performance and safety. Here, the type of secondary battery is not particularly limited, but it is particularly suitable for batteries using a metallic lithium negative electrode, since it can achieve both high energy density and safety. In addition, it is suitable for use in batteries in which different electrolytes are used on the positive electrode side and the negative electrode side, and in batteries in which dissolved materials and by-reaction products generated at the other electrode adversely affect the other electrode. Specifically, it is preferable to use it in a two-liquid battery, a lithium-sulfur battery, a clay battery, a metallic lithium-air battery, etc.
[0062] The secondary battery according to the embodiment of the present invention can be suitably used as a power source for small electronic devices such as mobile terminals, vehicles such as electric vehicles (EVs), hybrid vehicles (HEVs), plug-in hybrid vehicles (PHEVs), and UAMs, large industrial equipment such as industrial cranes, and unmanned transport vehicles such as drones and HAPS (High Altitude Platform Stations). It can also be suitably used as a power storage device for leveling power in solar cells, wind power generation devices, and the like, and for smart grids. The secondary battery according to the embodiment of the present invention is particularly preferably used in vehicles, electronic devices, and unmanned transport vehicles that require light weight. That is, the present invention can include an article including the secondary battery according to the embodiment of the present invention. The article is preferably one or more selected from the group consisting of electronic devices, vehicles, industrial equipment, unmanned transport vehicles, and power storage devices, and is particularly preferably one or more selected from the group consisting of vehicles, electronic devices, and unmanned transport vehicles.
[0063] Next, a method for producing an electrode composite in an embodiment of the present invention will be described. The method for producing an electrode composite in an embodiment of the present invention is not particularly limited, but includes, for example, a method using a polymer composition having a polymer whose main chain contains aromatic and heteroatoms and a solvent. Examples of the method for producing an electrode composite include a method of laminating a film obtained from the above-mentioned polymer composition to metal Li by pressing or the like, a method of applying the polymer composition to metal Li and then drying the volatile components of the polymer composition, and a method of electrolytically depositing or vapor-depositing Li on a film obtained from the above-mentioned polymer composition. The film that becomes the polymer layer can also be produced by applying the polymer composition to a substrate, drying the volatile components of the polymer composition, and peeling it off from the substrate. Among them, since the polymer layer can be formed thinly and uniformly without defects, it is preferable that the method for producing an electrode composite includes a step of applying the polymer composition to an electrode. This is because the step of peeling off the polymer layer, which is a cause of the occurrence of defects and the increase in surface roughness, from the substrate and transferring it onto the electrode is unnecessary.
[0064] In addition, as one aspect of the present invention, a polymer composition having a polymer whose main chain contains aromatic rings and heteroatoms and a solvent can be mentioned. The polymer contained in the polymer composition according to the embodiment of the present invention contains aromatic rings and heteroatoms in the main chain. When an electrolyte is used in a secondary battery, a known polymer can be used as necessary as long as it does not dissolve in the electrolyte. Such a polymer can be exemplified as the polymer exemplified as the polymer constituting the polymer layer of the electrode composite described above. Specific examples include polycarbonate, polyacetal, polyester, polysulfone, polyarylate, polyurethane, polyimide, polyamide (including polyamic acid), polyarylene sulfide, polyphenylene sulfide, polyamideimide, polyether ether ketone, polyetherimide, polyethersulfone, polyarylene ether, polyarylene ether ketone, and other polyethers, polyethylene, polypropylene, polymethyl methacrylate, and other vinyl polymers, as well as alloys and copolymers thereof. The polymer contained in the polymer composition according to the embodiment of the present invention is preferably composed of one or more selected from the group consisting of polyphenylene sulfide, polyamide, polyarylene ether, polyether sulfone, polyimide, polyamideimide, polyarylene ether ketone, and copolymers thereof, from the viewpoint of excellent heat resistance among these. In terms of excellent moldability, polyamide, polyphenylene sulfide, polyamideimide, and polyether sulfone are more preferable, and among these, aromatic polyamide, aromatic polyimide, and aromatic polyamideimide are particularly preferable from the viewpoint of excellent heat resistance and solvent resistance, and among these, aromatic polyamide (aramid) is most preferable from the viewpoint of high strength. These polymers may be used alone or in combination. For example, different types of polymers may be copolymerized, or may be alloyed in the film.
[0065] The polymer contained in the polymer composition according to the embodiment of the present invention preferably has at least one of a thiocarbonyl group, a thiourea group, a thioamide group, and a thiourethane group, and a thiourea group is particularly preferred. By having the above functional group, the interaction between the polymer and anion becomes large, and the cationic transport number is improved. The improvement of the cationic transport number reduces decomposition products during battery operation, and improves the battery life. In particular, a polymer having an aromatic ring on the main chain can be preferably used. Examples of the polymer having an aromatic ring on the main chain include aromatic polythioketone, aromatic polythiourea, aromatic polythioamide, aromatic polythiourethane, semi-aromatic polythioketone, semi-aromatic polythiourea, semi-aromatic polythioamide, and semi-aromatic polythiourethane. A blend of multiple polymers may also be used. Among them, aromatic polythiourea, aromatic polythioamide, aromatic polythiourethane, and semi-aromatic polythiourea are more preferred, and aromatic polythiourea is particularly preferred, because they tend to maintain high strength when thinned. That is, it is preferable that the ion-conducting polymer according to the embodiment of the present invention contains aromatic polythiourea.
[0066] The polymer composition according to the embodiment of the present invention preferably contains a fluorine generator. - It is a compound that generates ions and mainly contains F atoms. Specific examples include LiPF6, LiBF4, LiTFSI, LiFSI, and fluoroethyl carbonate. F - LiPF6, LiFSI, and fluoroethyl carbonate, which easily generate ions, are more preferable, LiPF6 and fluoroethyl carbonate are even more preferable, and LiPF6 is particularly preferable. By using a polymer composition containing a fluorine generator in the preparation of an electrode composite, the fluorine generator can be contained in the polymer layer of the electrode composite, thereby improving the battery life.
[0067] The weight ratio of the polymer contained in the polymer composition according to the embodiment of the present invention is preferably 0.1% by weight or more and 13.0% by weight or less, more preferably 1.0% by weight or more and 13.0% by weight or less, and more preferably 1.0% by weight or more and 8.0% by weight or less, from the viewpoint of film-forming property and resistance of the obtained electrode composite. By reducing the polymer concentration, the thickness of the obtained polymer layer can be reduced, and the resistance of the electrode composite can be reduced. On the other hand, by increasing the polymer concentration, the film-forming property becomes good.
[0068] The logarithmic viscosity of the polymer contained in the polymer composition according to the embodiment of the present invention is preferably 0.5 to 10.0 dL / g, more preferably 1.0 to 10.0 dL / g, more preferably 1.5 to 10.0 dL / g, more preferably 1.5 to 5.0 dL / g, and particularly preferably 1.5 to 4.0 dL / g. By setting the logarithmic viscosity within the above range, an electrode composite having excellent toughness and strength and excellent ion conductivity can be obtained. In addition, by setting the logarithmic viscosity within the above range, a high viscosity can be obtained even if the polymer concentration is low, and a thin polymer layer can be uniformly formed. As a result, the life of a battery produced with the obtained electrode composite is improved.
[0069] The solvent contained in the polymer composition according to the embodiment of the present invention preferably contains a solvent having a boiling point of 0° C. or more and less than 150° C., more preferably contains a solvent having a boiling point of 0° C. or more and less than 120° C., more preferably contains a solvent having a boiling point of 0° C. or more and less than 100° C., more preferably contains a solvent having a boiling point of 0° C. or more and less than 85° C., and particularly preferably contains a solvent having a boiling point of 0° C. or more and less than 60° C. By containing the above solvent, the solvent evaporates instantly, thereby forming a polymer layer with small surface roughness. Specific examples of solvents having a boiling point of 0° C. or more and less than 150° C. include acetone, methyl ethyl ketone, acetonitrile, 1,4-dioxane, tetrahydrofuran, dimethoxyethane, diethyl carbonate, and dimethyl carbonate.
[0070] The solvent contained in the polymer composition according to the embodiment of the present invention preferably contains solvent A having a boiling point of 0°C or more and less than 150°C, and solvent B having a boiling point of 150°C or more and 300°C or less. By containing solvent B, the polymer can be efficiently dissolved, the composition becomes homogeneous, and a homogeneous polymer layer can be formed. Specific examples of solvent B include N-methylpyrrolidone, N,N-dimethylacetamide, dimethylformamide, dimethylsulfoxide, sulfolane, propylene carbonate, and ethylene carbonate. In addition, from the viewpoint of evaporation rate, the boiling point of solvent B is more preferably 200°C or less, and even more preferably 180°C or less.
[0071] The solvent A and the solvent B contained in the polymer composition according to the embodiment of the present invention are preferably an azeotropic composition. The azeotropic composition improves the evaporation rate by simultaneously evaporating the solvents A and B, and an electrode composite having a uniform polymer layer is obtained. Specific examples of the azeotropic composition include ethylene glycol and toluene, acetamide and ortho-xylene, and ethylene glycol and chlorobenzene.
[0072] The moisture content of the polymer composition according to the embodiment of the present invention is preferably 0 ppm or more and less than 200 ppm, more preferably less than 100 ppm, even more preferably less than 50 ppm, and particularly preferably less than 10 ppm. A small moisture content can suppress an increase in surface roughness when the polymer composition is applied onto metallic Li. A method for reducing the moisture content of the polymer composition includes a method of mixing a polymer or solvent with a small moisture content in a glove box or dry room filled with an inert atmosphere.
[0073] In the embodiment of the present invention, a method for obtaining a polymer that can be used as a polymer layer of an electrode composite will be described using aromatic polyamide, aromatic polyimide, or their precursor polyamic acid as an example, although the polymer that can be used and the polymerization method thereof are not limited thereto.
[0074] Various methods are available for obtaining aromatic polyamides. For example, when using low-temperature solution polymerization with acid dichloride and diamine as raw materials, the polyamides are synthesized in aprotic polar organic solvents such as N-methylpyrrolidone, N,N-dimethylacetamide, dimethylformamide, and dimethylsulfoxide. In the case of solution polymerization, in order to obtain a polymer with a high molecular weight, it is preferable to set the water content of the solvent used for polymerization to 500 ppm or less (weight basis, the same applies below), more preferably 200 ppm or less. Furthermore, a metal salt may be added to promote dissolution of the polymer. As the metal salt, a halide of an alkali metal or alkaline earth metal that dissolves in an aprotic organic polar solvent is preferable, and examples of the metal salt include lithium chloride, lithium bromide, sodium chloride, sodium bromide, potassium chloride, and potassium bromide. When the acid dichloride and diamine are used in equal amounts, a polymer with an ultra-high molecular weight may be produced, so it is preferable to adjust the molar ratio so that one is 95.0 to 100.0 mol% of the other. In addition, the polymerization reaction of aromatic polyamide is accompanied by heat generation, and if the temperature of the polymerization system rises, a side reaction may occur and the degree of polymerization may not rise sufficiently, so it is preferable to cool the temperature of the solution during polymerization to 40° C. or less. Furthermore, when acid dichloride and diamine are used as raw materials, hydrogen chloride is by-produced in the polymerization reaction, and in order to neutralize this, it is recommended to use an inorganic neutralizing agent such as lithium carbonate, calcium carbonate, calcium hydroxide, or an organic neutralizing agent such as ethylene oxide, propylene oxide, ammonia, triethylamine, triethanolamine, diethanolamine, etc.
[0075] On the other hand, when the aromatic polyimide or its precursor polyamic acid that can be used in the embodiment of the present invention is polymerized using, for example, a tetracarboxylic anhydride and an aromatic diamine as raw materials, a method of synthesis by solution polymerization in an aprotic organic polar solvent such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, dimethylformamide, dimethylsulfoxide, etc. can be adopted. Since an ultra-high molecular weight polymer may be generated when the raw materials tetracarboxylic anhydride and aromatic diamine are used in equal amounts, it is preferable to adjust the molar ratio so that one is 90.0 to 99.5 mol% of the other. In addition, the polymerization reaction is accompanied by heat generation, and if the temperature of the polymerization system rises, precipitation may occur due to the imidization reaction, so it is preferable to keep the temperature of the solution during polymerization at 70°C or less. As a method of imidizing the aromatic polyamic acid synthesized in this way to obtain an aromatic polyimide, heat treatment, chemical treatment, or a combination of them is used. The heat treatment method is generally a method of imidizing polyamic acid by heating it at about 100 to 500°C. On the other hand, chemical treatments include a method using a tertiary amine such as triethylamine as a catalyst and a dehydrating agent such as a non-aromatic acid anhydride or an aromatic acid anhydride, or a method using an imidizing agent such as pyridine.
[0076] The logarithmic viscosity η of the aromatic polyamide and aromatic polyimide or the polyamic acid precursor thereof is preferably 0.5 to 10.0 dL / g, more preferably 1.5 to 5.0 dL / g, and particularly preferably 1.5 to 4.0 dL / g. By setting the viscosity within the above range, a polymer excellent in toughness and strength and excellent ion conductivity can be obtained. In addition, by setting the viscosity within the above range, a high viscosity can be obtained even if the polymer concentration is low, and it becomes easy to form a thin polymer layer. As a result, the effect of improving the life of a battery made from the obtained electrode composite can be obtained.
[0077] Next, a method for forming a polymer layer according to an embodiment of the present invention will be described. As described above, the polymer layer may be formed by directly applying a polymer composition to an electrode such as metallic lithium and drying the polymer composition, or by applying the polymer composition to a substrate such as a release film, peeling the polymer layer from the substrate after drying, and attaching the polymer layer to an electrode such as metallic lithium by roll pressing.
[0078] The polymer composition after polymerization may be used as it is for the film-forming solution, but when the solution contains a large amount of unnecessary substances such as neutralization salts, it is preferable to isolate the polymer once and then redissolve it in an organic solvent such as the above-mentioned aprotic organic polar solvent or sulfuric acid before use. The method for isolating the polymer is not particularly limited, but examples include a method in which the polymer solution after polymerization is added in small amounts to a large amount of water to extract the solvent and neutralization salts into the water, and only the precipitated polymer is separated and then dried. The polymer solid from which unnecessary substances such as neutralization salts have been removed can be used as a film-forming raw material by dissolving it again in a good solvent.
[0079] It is preferable to add lithium element to the polymer composition before film formation. By this operation, lithium element is contained at a concentration of 50 μg or more in 1 g of the obtained polymer composition, and the ionic conductivity of the polymer layer in the obtained electrode composite is improved. The method of adding such lithium element is not particularly limited, but examples include a method of adding lithium metal or lithium salt to the polymer composition. Here, the lithium salt is not particularly limited, but examples include LiPF6, LiAsF6, LiClO4, LiBF4, LiBr, lithium bis(oxalate)borate, lithium difluoro(oxalate)borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide, etc. The amount of lithium added is preferably 50 μg or more per 1 g of polymer weight, and it is more preferable that the content of lithium element in the polymer layer of the obtained electrode composite is in the above-mentioned preferred range.
[0080] The polymer composition prepared as described above, preferably the polymer composition after removing unnecessary substances and adding lithium element, etc., can be formed into a film by the so-called solution film-forming method. The solution film-forming method includes dry-wet method, dry method, wet method, etc., but it is preferable to use the dry method from the viewpoint of suppressing the elution of lithium element, etc. from the electrolyte layer. In the drying step for removing the solvent, the drying conditions may be a drying temperature and drying time that do not decompose the polymer and additives such as lithium salt, and are preferably within the range of, for example, 50 to 220 ° C. and 120 minutes. However, when a polyamic acid polymer is used and a film made of polyamic acid is to be obtained without imidization, the drying temperature is preferably 50 to 150 ° C. In any polymer, the drying conditions are more preferably 50 to 130 ° C. under reduced pressure.
[0081] Through these steps, the polymer layer of the electrode composite described above is obtained.
[0082] Next, a method for producing a composite ion-permeable membrane having a polymer layer on at least one side of an inorganic ion conductor will be described.
[0083] A composite ion-permeable membrane having a polymer layer on at least one side of an inorganic ion conductor can be obtained, for example, by applying the polymer composition obtained by the above-mentioned method to the surface of an inorganic ion conductor and removing the solvent. In this case, a known method can be used as the application method. Any known method can be used for removing the solvent, but since using water washing or solvent washing may cause elution of lithium element or deactivation of the inorganic ion conductor, it is preferable to volatilize at a temperature of 50°C or more and 220°C or less. More preferably, it is 50 to 130°C under reduced pressure. An electrode composite can be produced by adhering the obtained composite ion-permeable membrane to an electrode by the above-mentioned method. EXAMPLES
[0084] The present invention will be described in more detail below with reference to examples. The physical properties of the examples were measured by the following methods.
[0085] (1) Ionic conductivity of the polymer layer Using an HS cell (manufactured by Hosen Co., Ltd.), a cell was fabricated by stacking an electrode composite with the polymer layer facing the counter electrode, 200 μL of non-aqueous electrolyte (1 M LiTFSI ethylene carbonate (EC) / diethyl carbonate (DEC) = 1 / 1), and a SUS (stainless steel) 304 electrode.
[0086] After leaving the cell at rest for 24 hours at 25°C, the AC impedance of the cell was measured at 25°C using an electrochemical tester (Biologic, model number: SP-150) under conditions of an amplitude of 10 mV and a frequency of 1 MHz to 10 mHz. The resistance value was read from a graph plotted on a complex plane and substituted into the following formula (i) to calculate the ionic conductivity. The measurement was performed five times, and the calculated average value was taken as the ionic conductivity.
[0087] σ = T0 / AR (i) σ: Ionic conductivity (S / cm) T0: Thickness of the polymer layer (cm) A: Electrode area (cm 2 ) R: Resistance value (Ω).
[0088] (2) Thickness of the polymer layer The thickness of the electrode composite was measured using a thickness gauge (VL-50 manufactured by Mitutoyo Corp.) The thickness of the polymer layer was determined as the thickness of the film remaining after the electrode composite was immersed in distilled water and the metallic Li was removed.
[0089] (3) Porosity of the polymer layer A cross section of the electrode composite of the embodiment was prepared by the BIB (Broad Ion Beam) method, and SEM observation was performed using a scanning electron microscope (Hitachi High-Tech S-4800) at a magnification of 10,000 times and an acceleration voltage of 1.0 kV. The sample was not subjected to conductive treatment. The observation area was a 10 μm wide continuous observation over the shortest distance from one surface to the other surface. The area where carbon atoms were detected by SEM-EDX measurement was determined to be the polymer layer, and the 1960 nm 2All pores with a diameter equal to or larger than 50 nm (equivalent circle diameter of 50 nm or more) were extracted, and the sum of the pore areas / cross-sectional area of the polymer layer×100 was taken as the porosity.
[0090] (4) Surface roughness of the polymer layer (arithmetic mean roughness Ra) The arithmetic mean roughness (hereinafter referred to as "Ra", unit: μm) was measured using a surface roughness measuring device (manufactured by TIME Corporation). Measurements were carried out three times for each sample under the following conditions, and the average value was calculated. Cutoff length: 0.25mm Rating length: 1.25mm A larger Ra value indicates lower surface smoothness.
[0091] (5) Solvent content and type of solvent contained in the polymer layer The electrode composite was subjected to TGA measurement using DTG-50 (Shimadzu Corporation). The measurement conditions were as follows: in a nitrogen atmosphere, the temperature was raised from room temperature to 200°C at a rate of 5°C / min, and then the temperature was maintained at 200°C for 2 hours. The weight loss was taken as the solvent content. The contained solvent components were identified by immersing the electrode composite in heavy water to extract the solvent, and the obtained extracted solution was 1 The solvent composition was identified by H-NMR measurement.
[0092] (6) Average Lithium Atomic Ratio in the Polymer Layer Rutherford backscattering spectroscopy (RBS) / nuclear reaction analysis (NRA) measurements of the electrode composite were performed using a Pelletron 5SDH-2 (National Electronics Corporation). In the depth profile of each composition, the average atomic % of Li in the region where the Li composition was 99 atomic % or less was measured. The measurement conditions were as follows: RBS measurements Incident ions: 4 He ++ Incident energy: 2300keV Incident angle: 0deg Scattering angle: 160deg Specimen current: 7nA Beam diameter: 2mm In-plane rotation: None Irradiance: 45μC Nuclear reaction:- NRA measurement Incident ions: H + Incident energy: 1500keV Incident angle: 0deg Scattering angle: 146deg Specimen current: 5nA Beam diameter: 2mm In-plane rotation: None Irradiance: 48μC Nuclear reaction: 7Li(p,α)4He.
[0093] (7) Inherent viscosity of the polymer composition The polymer was dissolved at a concentration of 0.5 g / dl in N-methyl-2-pyrrolidone (NMP) containing 2.5 wt% lithium bromide (LiBr), and the flow time was measured at 30° C. using an Ubbelohde viscometer. The flow time of a blank LiBr 2.5 wt% / NMP in which no polymer was dissolved was also measured in the same manner, and the logarithmic viscosity ηinh (dl / g) was calculated using the following formula.
[0094] Logarithmic viscosity ηinh(dl / g)=[ln(t / t0)] / 0.5 t0: Blank flow time (seconds) t: sample flow time (sec).
[0095] (9) Moisture content of polymer composition The moisture content was measured using a Karl Fischer moisture meter (AQV-7, manufactured by Hiranuma Sangyo Co., Ltd.) The amount of moisture in the charged polymer composition was quantified, and the moisture content was calculated from the obtained value.
[0096] (10)XPS analysis The polymer layer was removed from the electrode, and the polymer layer was ion-etched from the surface close to the electrode to the other surface while performing XPS analysis to analyze the atomic composition of each layer. Ion etching allows the atomic species to be calculated from the peak position of each bond energy, and the atomic ratio to be calculated from the peak intensity. For example, Li+ ions, 55 eV, Li metal, 53 eV, F - The ion peak is seen at 684 eV. The measurement conditions and ion etching conditions are as follows. The thickness of the ion-etched layer was calculated from the etching time per etching and the etching rate calculated from the analysis of polymethyl methacrylate (PMMA). Measurement conditions Equipment: PHI Genesis (Ulvac-PHI) Excitation X-ray: monochromatic Al K 1,2 line (1486.6 eV) X-ray diameter: 200 μm Photoelectron detection angle: 90° (detector angle relative to sample surface) Ion etching conditions Ion species: Ar gas cluster ion (Ar-GCIB) Voltage: 10 kV Etching time per cycle: 0.4min Etching rate: 54.2 nm / min (PMMA equivalent value).
[0097] (11) Dendrite resistance When the electrode composite contained metallic lithium, an HS cell (manufactured by Hosen Co., Ltd.) was used, and two sheets of the electrode composite were laminated on both sides of a polyolefin microporous film (thickness 25 μm, air permeability 191 sec / 100 cc, manufactured by Toray) so that the polymer layers faced each other, and 300 μL of 1M LiTFSI EC / DEC = 1 / 1 (volume ratio) was injected and sealed. A current density of 0.5 mA / cm was measured using a charge / discharge test device (HJ1005SM8A, manufactured by Hokuto Denko Co., Ltd.). 2 The test was conducted for 50 cycles with a charge / discharge time of 1 hour. If the battery operated for 100 cycles without exceeding the overvoltage conditions (3V or more, -2V or less), it was rated as "Excellent: ◎", if it operated for 50 to less than 100 cycles, it was rated as "Pass: ○", and if it operated for less than 50 cycles, it was rated as "Fail: ×".
[0098] When the electrode composite does not contain metallic lithium, an HS cell (manufactured by Hosen Co., Ltd.) was used, metallic Li was placed on one side of a polyolefin microporous film (thickness 25 μm, air permeability 191 sec / 100 cc, manufactured by Toray) and one sheet of electrode composite was placed on the other side so that the polymer layer was the counter electrode side, and 300 μL of 1M LiTFSI EC / DEC = 1 / 1 (volume ratio) was injected and sealed. A charge / discharge test was performed using a charge / discharge test device (HJ1005SM8A, manufactured by Hokuto Denko Co., Ltd.) with metallic Li as the positive electrode and the electrode composite as the negative electrode, with a current density of 0.1 mA / cm. 2 A charging current was passed for 40 hours to deposit metallic lithium on the electrode composite. Next, using an HS cell (manufactured by Hosen Co., Ltd.), two sheets of the electrode composite with deposited metallic lithium were laminated on both sides of a polyolefin microporous film (thickness 25 μm, air permeability 191 sec / 100 cc, manufactured by Toray) so that the polymer layers faced each other, and 300 μL of 1M LiTFSI EC / DEC = 1 / 1 (volume ratio) was injected and sealed. A current density of 0.5 mA / cm was measured using a charge / discharge test device (HJ1005SM8A, manufactured by Hokuto Denko Co., Ltd.). 2 The test was conducted for 50 cycles with a charge / discharge time of 1 hour. If the battery operated for 100 cycles without exceeding the overvoltage conditions (3V or more, -2V or less), it was rated as "Excellent: ◎", if it operated for 50 to less than 100 cycles, it was rated as "Pass: ○", and if it operated for less than 50 cycles, it was rated as "Fail: ×".
[0099] (Reference Example 1) Polymerization of Polymer P-1 4,4'-diaminodiphenyl ether (manufactured by Tokyo Chemical Industry Co., Ltd.) was dissolved as a diamine in dehydrated NMP (N-methyl-2-pyrrolidone, manufactured by Mitsubishi Chemical Co., Ltd.) under a nitrogen stream and cooled to 30°C or less. 2-chloroterephthaloyl chloride (manufactured by Nippon Light Metal Co., Ltd.) equivalent to 100 mol% relative to the total amount of diamine was added thereto over 60 minutes while maintaining the system at 30°C or less under a nitrogen stream, and after the entire amount was added, the mixture was stirred for about 1 hour to polymerize an aromatic polyamide. The obtained polymerization solution was neutralized with 97 mol% lithium carbonate (manufactured by Honjo Chemical Co., Ltd.) and 6 mol% diethanolamine (manufactured by Tokyo Chemical Industry Co., Ltd.) relative to the total amount of acid chloride to obtain a polymer solution. The obtained polymer solution was poured into purified water in a weight ratio of 10 times or more, the solvent and neutralization salt were extracted into water, and only the precipitated polymer was separated, and then vacuum dried at 80°C for 10 hours to obtain polymer P-1. The inherent viscosity η of the obtained polymer was 2.3 dL / g.
[0100] (Reference Example 2) Polymerization of Polymer P-2 Polymerization was carried out in the same manner as in Reference Example 1, except that the diamine used was 1,4-bis(4-aminophenoxy)benzene, to obtain polymer P-2. The inherent viscosity η of the obtained polymer was 2.3 dL / g.
[0101] (Reference Example 3) Polymerization of Polymer P-3 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl (manufactured by Tokyo Chemical Industry Co., Ltd.) was dissolved as a diamine in dehydrated NMP (N-methyl-2-pyrrolidone, manufactured by Mitsubishi Chemical Co., Ltd.) under a nitrogen stream and cooled to 30°C or lower. 2-fluoroterephthalic acid chloride (manufactured by Ihara Nikkei Chemical Industry Co., Ltd.) equivalent to 98.5 mol% based on the total amount of diamine was added thereto over 60 minutes while maintaining the system at 30°C or lower under a nitrogen stream, and after the entire amount was added, the mixture was stirred for about 1 hour to polymerize aromatic polyamide. The obtained polymerization solution was neutralized with 97 mol% lithium carbonate (manufactured by Honjo Chemical Co., Ltd.) and 6 mol% diethanolamine (manufactured by Tokyo Chemical Industry Co., Ltd.) based on the total amount of acid chloride to obtain a polymer solution. The obtained polymer solution was poured into 10 times or more of purified water by weight ratio, the solvent and neutralization salt were extracted into water, and only the precipitated polymer was separated and then vacuum dried at 80°C for 10 hours to obtain polymer P-2. The inherent viscosity η of the obtained polymer was 3.8 dL / g.
[0102] (Reference Example 4) Polymerization of Polymer P-4 In dehydrated NMP (N-methyl-2-pyrrolidone, manufactured by Mitsubishi Chemical Corporation), 4,4'-diaminodiphenyl ether (manufactured by Tokyo Chemical Industry Co., Ltd.) was dissolved as a diamine under a nitrogen stream, and 1,4-phenylenedithioisocyanate (manufactured by Tokyo Chemical Industry Co., Ltd.) equivalent to 100 mol% relative to the total amount of diamine was added thereto under a nitrogen stream in the system over 5 min, and after the total amount was added, the mixture was stirred for about 7 hours to polymerize aromatic polythiourea (polymer P-4). In addition, the total concentration of 4,4'-diaminodiphenyl ether and 1,4-phenylenedithioisocyanate in the polymerization solution was set to 19 wt%. The logarithmic viscosity ηinh of the obtained polymer was 1.5 dl / g. Next, this polymer solution was poured into ethanol at a mass ratio of 10 times or more, the solvent and unreacted matter were extracted into ethanol, and only the precipitated polymer was separated, and then vacuum dried at 60 ° C for 10 hours to obtain a polymer powder.
[0103] (Reference Example 5) Polymerization of Polymer P-5 A polymer powder was obtained in the same manner as in Reference Example 4, except that tetramethylenediamine (manufactured by Tokyo Chemical Industry Co., Ltd.) was used in place of 4,4'-diaminodiphenyl ether to polymerize a semi-aromatic polythiourea (polymer P-5).
[0104] (Reference Example 6) Polymerization of Polymer P-6 A polymer powder was obtained in the same manner as in Reference Example 4, except that isophthaloyl chloride (manufactured by Tokyo Chemical Industry Co., Ltd.) was used in place of 2-chloroterephthaloyl chloride to polymerize (Polymer P-6).
[0105] Example 1 Polymer P-1 5.0% by weight, LiTFSI (Fujifil Wako Pure Chemical, for organic synthesis) 2.5% by weight, DMF (Fujifil Wako Pure Chemical, ultra-dehydrated, for organic synthesis, boiling point 153 ° C.) 85.5% by weight, acetone (Fujifil Wako Pure Chemical, ultra-dehydrated, for organic synthesis, boiling point 56 ° C.) 7.0% by weight were weighed in a glove box (dew point -75 ° C. or less, oxygen concentration 0.02 ppm or less) and sealed in a 30 mL screw bottle. The polymer composition in the screw bottle was stirred using a planetary mixer (THINKY, AR-250) until no solid matter was present, to obtain a polymer composition.
[0106] (Examples 2 to 9, Comparative Examples 1 to 3) A polymer composition was prepared in the same manner as in Example 1 so as to have the composition shown in Table 1. LiPF6 and fluoroethylene carbonate were used for battery research manufactured by Fujifilm Wako Pure Chemical Industries. NMP (boiling point 202°C) and THF (boiling point 66°C) were used as ultra-dehydrated products for organic synthesis manufactured by Fujifilm Wako Pure Chemical Industries.
[0107] Example 10 The polymer composition prepared in Example 1 was applied to a metallic lithium foil (Honjo Metal, thickness 200 μm, circular diameter 16 mm) in the form of a film so that the polymer layer after vacuum drying would be 1 μm thick, and the film was left to stand on a hot stage at 80° C. for 1 hour, and then dried in a vacuum dryer at 130° C. for 1 hour. All of the above operations were carried out in a glove box (dew point below -50° C., oxygen concentration below 100 ppm). The characteristics of the obtained electrode composite are shown in Table 2.
[0108] Example 11 An electrode composite was produced in the same manner as in Example 10, except for using the polymer composition produced in Example 2. The characteristics of the obtained electrode composite are shown in Table 2.
[0109] Example 12 An electrode composite was produced in the same manner as in Example 10, except that the polymer composition produced in Example 3 was used and the thickness of the polymer layer after vacuum drying was 2 μm. The characteristics of the obtained electrode composite are shown in Table 2.
[0110] (Example 13) The polymer composition prepared in Example 3 was applied to a glass plate as a support in the form of a film so that the thickness of the polymer layer after vacuum drying was 5 μm, and the film was dried in a hot air oven at 130 ° C until the film had self-supporting properties, and then the film was peeled off from the support. Next, the peeled film was fixed to a metal frame and dried in a vacuum dryer at 130 ° C for 0.5 hours to prepare a polymer layer. The obtained polymer layer was vacuum dried at 25 ° C for 12 hours, and then 50 μL of dioxane (Fujifil Wako Pure Chemical, dehydrated, for organic synthesis) was dropped onto a metallic lithium foil (Honjo Metal Co., Ltd., thickness 200 μm, circular diameter 16 mm) in a glove box, and then the prepared polymer layer was placed on the metallic lithium foil and bonded with a roller. The obtained laminate was dried in a vacuum dryer at 130 ° C for 0.5 hours. The characteristics of the obtained electrode composite are shown in Table 2.
[0111] Example 14 The polymer composition prepared in Example 4 was applied to a release film as a support so that the thickness of the polymer layer after vacuum drying was 2 μm, and vacuum drying was performed at 60 ° C for 1 hour. The above work was performed in a dry room (dew point -50 ° C or less). In a glove box, the release film was peeled off from the support, and 50 μL of dioxane (Fujifil Wako Pure Chemical, dehydration, for organic synthesis) was dropped onto a metallic lithium foil (Honjo Metal Co., Ltd., thickness 200 μm, circular diameter 16 mm), and then the prepared polymer layer was placed on the metallic lithium foil and adhered with a roller. The obtained laminate was dried in a vacuum dryer at 130 ° C for 1.0 hour. The characteristics of the obtained electrode composite are shown in Table 2.
[0112] Example 15 An electrode composite was produced in the same manner as in Example 14, except for using the polymer composition produced in Example 5. The characteristics of the obtained electrode composite are shown in Table 2.
[0113] Example 16 The electrode composite prepared in Example 12 was placed in an HS cell (manufactured by Hosen Co., Ltd.), 300 μL of 1M LiPF6EC / DEC was dropped, and the cell was sealed. After leaving the cell at 60° C. for 24 hours, the electrode composite was taken out and dried in a vacuum at 130° C. for 1.0 hour to dry the electrode composite. The characteristics of the obtained electrode composite are shown in Table 2. The results of the XPS analysis are shown in FIG. 1. In the region up to a depth of about 500 nm, including the surface layer (depth 0 nm to 300 nm) of the surface having the electrodes in close proximity, Li + Atoms and F - The abundance ratio of each atom had a region where it was 5% or more.
[0114] (Example 17) Except for using copper foil instead of metallic lithium, an electrode composite was produced in the same manner as in Example 11. The characteristics of the obtained electrode composite are shown in Table 2.
[0115] (Example 18) An electrode composite was produced in the same manner as in Example 10, except for using the polymer composition produced in Example 6. The characteristics of the obtained electrode composite are shown in Table 3.
[0116] (Example 19) An electrode composite was produced in the same manner as in Example 10, except for using the polymer composition produced in Example 7. The characteristics of the obtained electrode composite are shown in Table 3.
[0117] (Example 20) An electrode composite was produced in the same manner as in Example 10, except for using the polymer composition produced in Example 8. The characteristics of the obtained electrode composite are shown in Table 3.
[0118] Example 21 An electrode composite was produced in the same manner as in Example 10, except for using the polymer composition produced in Example 9. The characteristics of the obtained electrode composite are shown in Table 3.
[0119] Comparative Example 4 An electrode composite was produced in the same manner as in Example 4, except that the polymer composition produced in Comparative Example 1 was used and the thickness of the polymer layer after drying was 5 μm. The characteristics of the obtained electrode composite are shown in Table 3.
[0120] Comparative Example 5 An electrode composite was produced in the same manner as in Example 4, except for using the polymer composition produced in Comparative Example 2. The characteristics of the obtained electrode composite are shown in Table 3.
[0121] Comparative Example 6 A 20 wt% NMP solution of polyethersulfone (Sumika Excel 5900P, manufactured by Sumitomo Chemical Co., Ltd.) was applied to a glass plate as a support in the form of a film so that the thickness of the polymer layer after drying was 10 μm, and after immersion in distilled water at 25 ° C for 15 minutes, the obtained polymer film was peeled off from the support and vacuum dried at 130 ° C for 1 hour. After vacuum drying at 25 ° C for 12 hours, 50 μL of dioxane (Fujifil Wako Pure Chemical, dehydration, for organic synthesis) was dropped onto a metallic lithium foil (Honjo Metal Co., Ltd., thickness 200 μm, circular diameter 16 mm) in a glove box, and then the prepared polymer ion conductive film was placed on the metallic lithium foil and bonded with a roller. The obtained laminate was dried in a vacuum dryer at 130 ° C for 0.5 hours. The characteristics of the obtained electrode composite are shown in Table 3.
[0122] Comparative Example 7 An electrode composite was produced in the same manner as in Example 7, except for using the polymer composition produced in Comparative Example 3. The characteristics of the obtained electrode composite are shown in Table 3.
[0123] (Preparation of model all-solid-state batteries) The electrode composites of Examples 5 and 6 were each enclosed in an all-solid-state battery cell (manufactured by Miklab) so that the metal Li foil (manufactured by Honjo Metal, thickness 200 μm, circular diameter 16 mm) was on the polymer layer side of the electrode composite. The AC impedance of the produced cells was measured at 25° C. using an electrochemical tester (manufactured by Biologic, model number: SP-150) under conditions of an amplitude of 10 mV and a frequency of 1 MHz to 10 mHz. The electrode composite of Example 5 had an ionic conductivity of 6.8×10 -7 S / cm, whereas in Example 6, no ionic conductivity was observed.
[0124] From Table 2, the electrode assemblies of Examples 10 to 21, which were produced using the polymer compositions of Examples 1 to 9, had better dendrite resistance than the electrode assemblies of Comparative Examples 4 to 7. In addition, the lithium atomic ratio was high, and Li + Atomic ratio and F - It was confirmed that electrode assemblies having regions in which both atomic ratios are 5% or more and 50% or less showed better results in cycle tests of dendrite resistance.
[0125]
Table 1
[0126]
Table 2
[0127]
Table 3
Claims
1. An electrode composite having a polymer layer and an electrode adjacent to at least one surface of the polymer layer, the electrode comprises metallic Li or a current collector; a polymer constituting the polymer layer contains an aromatic ring and a heteroatom in a main chain, The ionic conductivity of the polymer layer is 1.0×10 -6 the porosity of the polymer layer observed by cross-sectional SEM is 0% or more and 10% or less, and the arithmetic mean roughness Ra of the surface of the polymer layer is 0 μm or more and 1.0 μm or less.
2. Li, as measured by X-ray photoelectron spectroscopy (XPS) analysis + Atomic ratio and F - The electrode composite according to claim 1 , wherein a region in which both atomic ratios are 5% or more and 50% or less is present on a surface layer of the polymer layer having the electrode in close proximity thereto, or is present between the polymer layer and the electrode.
3. 2. The electrode composite according to claim 1, wherein the solvent content in the polymer layer is from 0% by weight to 60% by weight.
4. 4. The electrode complex according to claim 3, wherein the solvent comprises at least one of N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethylacetamide (DMAc), dimethylsulfoxide (DMSO), and sulfolane.
5. 2. The electrode composite of claim 1, wherein the polymer is an aromatic polyamide having the structure: 【Chemistry 1】 Ar 1 and Ar 2 Ar is a structure containing an aromatic ring in a part of the main chain. 1 and Ar 2 may have the same structure or different structures. 1 and Ar 2 For example, a plurality of aromatic rings may be bonded together by ether bonds or the like, and a non-aromatic group bonded to an aromatic ring may be included in the main chain.
6. 6. The electrode composite of claim 5, wherein the aromatic polyamide has the following chemical structure: 【Chemistry 2】 R 1 ~R 4 are functional groups composed of one or more of C, H, O, N, Si, S, and halogen atoms.
7. 2. The electrode composite according to claim 1, wherein the polymer is a polymer having a thiourea group.
8. 2. The electrode composite according to claim 1, wherein the polymer layer has a thickness of 0.1 μm or more and 50.0 μm or less.
9. 2. The electrode composite according to claim 1, wherein the average lithium atomic ratio of the polymer layer is 0.005 or more and 1.0 or less.
10. A polymer composition comprising a polymer whose main chain contains aromatic and heteroatoms, and a solvent.
11. The polymer composition of claim 10 comprising a fluorine generator.
12. The polymer composition of claim 10, wherein the polymer comprises thiourea groups.
13. The polymer composition according to claim 10, wherein the solvent comprises a solvent having a boiling point of 0°C or more and less than 150°C.
14. The polymer composition according to claim 10, wherein the solvent comprises a solvent A having a boiling point of 0° C. or more and less than 150° C., and a solvent B having a boiling point of 150° C. or more and 300° C. or less.
15. The polymer composition according to claim 14, wherein said solvent A and said solvent B are an azeotropic composition.
16. The polymer composition of claim 10, wherein the polymer is an aromatic polyamide.
17. The polymer composition according to claim 10, having an inherent viscosity of 1.5 dl / g or more and 10 dl / g or less.
18. The polymer composition according to claim 10, wherein the weight ratio of the polymer is from 0.1% by weight to 13.0% by weight.
19. The polymer composition according to claim 10, having a moisture content of 0 ppm or more and less than 200 ppm.
20. A method for producing an electrode composite comprising the step of applying the polymer composition of claim 10 to an electrode.
21. A battery comprising the electrode composite of claim 1.
22. A vehicle, unmanned transport vehicle, electronic device, or power storage device comprising the battery of claim 21.
Citation Information
Patent Citations
Lithium metal anode for lithium battery
JP2004134403A
Solid electrolyte-containing layer
JP2021163622A